EDUCATION ON VARIOUS ALTERNATIVE SOURCES OF FUNDING FOR MSME DEVELOPMENT (CASE STUDY OF SRENGAT DISTRICT, BLITAR REGENCY): Edukasi Berbagai Alternatif Sumber Pendanaan untuk Pengembangan UMKM (Studi Kasus Kecamatan Srengat, Kabupaten Blitar) - Yenny Kornitasari; Munawar (P3M Politeknik Negeri Malang, 2026)
MSMEs (Micro, Small, and Medium Enterprises) are an essential economic pillar in many countries, including Indonesia. However, many MSMEs face challenges accessing capital due to limited bank credit services and the risk of loan defaults. Alternative solutions such as cooperatives and FinTech are beginning to be considered to fulfill the capital needs of MSMEs. Capitalization is emphasized as a crucial factor for the growth and innovation of MSMEs, aiding in business expansion, product innovation, quality improvement, and effective marketing strategies. In Srengat Subdistrict, Blitar District, the research team aims to provide socialization and education about various alternative funding sources for MSMEs, such as MSME Cooperatives and financial technology, so local MSMEs can grow and contribute more to the economy.